The role of local councils in promoting overall development in the Kingdom of Saudi Arabia - Khulais Governorate as a model - Albeladi, Yousef Khudair (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to identify the role of the local council in achieving the local development in Khulais governorate and the degree of interaction and interest of civil society to participate in local development, and overcome its obstacles. The study was approved the descriptive analytical method in conducting this study, where the questionnaire was used to collect the initial data from the study population, which consisted of All Saudi population in Khulaisgovernorate who are over or equal to 20 years of age, and whose number reached 38,250 people. A simple random sample of 380 citizens was chosen, the questionnaires were then unloaded and analyzed using SPSS Statistical Package and the use of appropriate statistical tests, in order to reach valuable indications and indicators supporting the subject of the study. The study reached several important results, the most important of which were: The existence of an impartial response by respondents regarding the degree of effectiveness of the role of local council of Khulais Governorate. There is a correlation between the role of local council and the four dimensions of overall development (the political dimension - the environmental dimension - the social dimension - the economic dimension) in Saudi Arabia - the council of the province of Khulais model, as the value of the correlation coefficients between the role of the local council and the four overall development dimensions were 0.816. In light of the results of the study, and after reference to the discussion of the main focus of the study, the study reached several recommendations as follows: Focus on targeting local council projects and services for lower social strata to provide them with a decent life. The need to work to increase the interest of the local council in the province to follow up on community and environmental issues within the province. Intensifying initiatives organized by the local council related to contributing to the development of the local economy.
Keywords: Development; Local Community; Municipality; Khulais Governorate; KSA